Gut microbiota-based biomarkers for precision subtype classification and mechanistic understanding of biliary and hyperlipidemic acute pancreatitis - Deng, Xinyu; Wu, Xueqian; Wang, Ruobing; Qiao, Xiaohan; Cao, Ting; Xu, Yao; Jin, Qun; Jia, Lingling; Liang, Wei (Frontiers in Microbiology, 2025)
BackgroundAcute pancreatitis (AP) is an inflammatory disorder with distinct etiological subtypes, yet the role of gut microbiota in disease pathogenesis remains poorly understood. We hypothesized that biliary acute pancreatitis (BAP) and hyperlipidemic acute pancreatitis (HLAP) exhibit etiology-specific gut microbiota signatures that correlate with disease severity and metabolic dysfunction.MethodsWe conducted a cross-sectional study in which stool samples were collected from 20 BAP patients, 20 HLAP patients, and 20 healthy controls (HC) for 16S rRNA gene sequencing to compare gut microbiota profiles among the three groups. Microbial diversity, taxonomy, and functional genes were analyzed using bioinformatics pipelines. Clinical-microbial correlations were assessed, and the construction of RF and logistic regression models evaluated diagnostic biomarker potential.ResultsBoth AP groups showed significantly reduced microbial diversity compared to controls, with HLAP patients exhibiting more severe dysbiosis. HLAP patients showed enrichment of pro-inflammatory taxa, including Escherichia-Shigella and Collinsella, alongside depletion of beneficial genera Faecalibacterium and Bifidobacterium. As a key SCFA-producing genus, Faecalibacterium exhibited comprehensive correlations with inflammatory markers, pancreatic enzymes, and lipid profiles in Spearman correlation analysis. Functional analysis revealed compromised short-chain fatty acid biosynthesis capacity, as evidenced by significant downregulation of acetate (ackA, pta) and butyrate (buk, but) synthesis genes in AP patients, which may have partially mediated the observed differences in microbiota composition. Furthermore, our findings reveal that multi-species biomarker panels provide superior diagnostic performance compared to single-species predictors for BAP and HLAP subtype classification.ConclusionBAP and HLAP patients exhibit distinct gut microbiota signatures with progressive dysbiosis, functional impairment, and strong host associations. These findings establish a novel framework linking gut microbial composition to AP pathophysiology, providing insights for microbiome-targeted precision medicine strategies.